STRATEGI PROMOSI UNTUK MENINGKATKAN MINAT BACA DI PERPUSTAKAAN SD ISLAM AL AZHAR 21 PONTIANAK - Kurniawan, Riko; Madeten, Sisilya Saman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research was conducted by writer to know the strategy of promotion conducted by islamic elementary school Al Azhar 21 Pontianak. The students especially through promotional programs that run by the library at islamic elementary school Al Azhar 21 Pontianak. In this research, the researcher used descriptive method with Qualitative Research Form. Qualitative method was a research that focuses on observation of events, complexly studied phenomena, unrecognizable social character. Techniques of collecting data used ware observation, documentation, direct interviews at the library of Islamic Elementary School Al Azhar 21 Pontianak. From the results of this study, it can be seen that promotional strategies can increase the interest in reading in the library of Islamic Elementary School Al Azhar 21 Pontianak. There were several ways used in promoting the library, one of them through the contests, the announcement of new books and the flagship program was mini libraries that were available in every classroom and also one of the new program in planed was a reading corner. Increasing interest in reading in the library was very important considering this school is a favorite school in the pontianak city. According to the librarian of the school, the strategy that has been implemented was quite effective, but of course must continue to be increased so that all parties in the school environment really support every promotion strategy that the library do. Keywords: Strategy , Promotion, library, Reading Interest.